which steps will translate f(x) = 3x to g(x) = 3x 1 4? shift f(x) = 3x one unit up and four units to the right. shift f(x) = 3x one unit up and four units to the left. shift f(x) = 3x one unit to the right and four units up. shift f(x) = 3x one unit to the left and four units up

Respuesta :

W0lf93
The expression for g(x) is wrong, you skipped some signs and, apparentely, some parentheses. The rigtht expression for g(x) should be g(x) = 3(x+1) + 4. Note that g(x) = 3(x+1) + 4 it is the same that f(x+1) + 4. When you add a number to the argument, the graph of function is shifted that number of units to the left; and when you add a number to the function the graph shifts that number of units up. Therefore, the steps that will translate f(x) = 3x to g(x) = 3(x+1) + 4 is shift f(x) one unit to the left and four units up.

The correct steps that will translate [tex]f(x)=3x \ to \ g(x) = (3x+1)+4[/tex] is one unit to the right and four units up

What is Translation and transformation?

Given the function h(x) = (3x+1)+4

The parent function is 3x.

For the expression 3x+1, this shows that the parent function translated 1 unit to the right.

Get the statement for the translation

For the function (3x+1)+4, there is a translation of one unit to the right and four units up

Hence the correct steps that will translate [tex]f(x)=3x \ to \ g(x) = (3x+1)+4[/tex] is one unit to the right and four units up

Learn more on translation here: https://brainly.com/question/1046778